The use of ECAP in the Microstructural Conditioning of the 355 Aluminum Alloy for Thixoforming* - Gregolin,A. (2020)
The purpose of this study is to analyze the use plastic deformation (ECAP - Equal Channel Angular Pressing) in the preparation of the 355 aluminum for posterior use in Thixoforming. For this purpose, the 355 alloy, in the as cast state and after a pass of ECAP was heated to temperatures of 575 and 595 °C, enough to produce 45 and 55% of liquid fraction, for times of 0, 30, 60 e 90s. In these conditions, it is possible to obtain a refined globular structure with the size of a grain, close to 75 µm, globule size of 55 µm and high sphericity (around 0.66), parameters which are excellent for this kind of processing. Hot compression tests at the same temperatures and holding times determine the rheological behavior. Maximum processing strain was obtained around 1 MPa for the sample in ECAped condition against 4 MPa of the as cast condition, which corresponds to maximum viscosity around 105 Pa.s, (molten glass, clay), inferior to the as cast condition (11.5 * 105 Pa.s). Therefore, the ECAPed 355 alloy is an easily conformable material very likely to be applied to semisolid processing.